MOTIFS EM REDES LITERÁRIAS - Viana, Mônica Aparecida Schicorski (2014)
The study of complex networks has been widely applied to various areas of science, such as biology, philosophy, sociology, technology, physics, chemistry, among others. We directed this study of networks for not much explored area, the area of literature. We apply the theory of complex networks in networks generated from the scansion of poetic works, more specifically sonnets of Camoens and Bocage. The aim is to identify structures of significant motifs within networks and observe the scope thereof in the work in its original structure. To identify these motifs, it was necessary to develop a method of locating motifs in networks that were not based on their recurrence, but in its significance within the structure. We then decided to use a standard measure in identifying poetic syllables, syllables that represent these network nodes, indicating the most relevant within each structure analyzed network. The measure chosen is called centrality of intermediation, it tells us how important a node within a network. After the identification of all significant motifs we performed the same location of the original structures of the works. The motifs were duly highlighted with different colors, allowing to analyze the sound of them and the authors define these characteristics by identifying a specific identity of each author. We were able to observe the end of the analysis that the developed method, based on the measure of the centrality of mediation was effective, since the significant motifs have wide scope in poetic structure of the analyzed works, demonstrating how to study a complex network is not necessary know it completely, just know the significant motifs that comprise it. Regarding the sound and finding an identity for each author, this result still remains vacant. It was possible to identify the sound partially in some works, but nothing that allows, decisively, set a specific identity for a given author.